Pemberdayaan Keluarga Prasejahtera Melalui Peningkatan Nilai Tambah Lahan Pekarangan - Tasril Bartin; Irmawita Irmawita; Wisroni Wisroni (RC-INSTITUT, 2020)
This paper is part of a report on community empowerment activities by a team from Padang State University with the focus of the activity being the empowerment of poor housewives through optimizing the function of the plot of land with economically valuable plants, located in Nagari Sungai Buluh Timur, Batang Anai District, Padang Pariaman District. The purpose of the empowerment program is to improve the behavior of poor housewives in order to be able to optimize the utilization of the potential of family resources including specifically the plots of land so that they can increase family income. This dedication activity took the form of counseling with lectures and discussions about the family and its problems, counseling, and workshops on the cultivation of garden plants. Overall Empowerment activities can go well according to plan. Participants were enthusiastic about optimizing the use of the yard, and there was support from the wider community and the village government for the sustainability of the program in the future.